2018
DOI: 10.1039/c8nr02328j
|View full text |Cite
|
Sign up to set email alerts
|

Room temperature p-orbital magnetism in carbon chains and the role of group IV, V, VI, and VII dopants

Abstract: The study of magnetism without the involvement of transition metals or rare earth ions is considered the key to the fabrication of next generation spintronic devices. Several recent reports claim that optimizing the occupation number of the mixed p-orbitals is the correct way to reinforce p-orbital magnetism in bulk crystals. We provide experimental evidence that the kinked monoatomic carbon chains, the so-called linear-chained carbon, generate intrinsic ferromagnetism even above room temperature. According to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 19 publications
2
26
0
Order By: Relevance
“…In particular, it was shown that one-dimensional carbon chains can have a strength, elastic modulus, and stiffness greater than any known material, including diamond, carbon nanotubes, and graphene, and make it possible to create new composite materials [22]. It is also assumed that carbines can be used to create field-effect transistors [25], and also show the possibility of possessing one-dimensional carbon chains with interesting magnetic [26] and electrical properties [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it was shown that one-dimensional carbon chains can have a strength, elastic modulus, and stiffness greater than any known material, including diamond, carbon nanotubes, and graphene, and make it possible to create new composite materials [22]. It is also assumed that carbines can be used to create field-effect transistors [25], and also show the possibility of possessing one-dimensional carbon chains with interesting magnetic [26] and electrical properties [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Although the magnetic moment of p-shell may be weak [6], the electrons that move less freely on p-shells allow a strong exchange coupling [5]. An experimental observation confirmed that the p-orbital ferromagnetism of the undoped monoatomic carbon chain persisted up to 400K, even though the magnetic moment of carbon is only ~0.2µ B [5].…”
mentioning
confidence: 98%
“…A. Bergara et al have verified that the optimized magnetic moment of the p-shell corresponds to a maximum overlap between the p-shells [1]. If the orbitaloverlap is too strong, the circulation motion of the electron is disturbed by a strong electrostatic repulsion which destroys the magnetic moment of p-shell [1,5].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Journal of Nanomaterials needed for carbyne production [8]. Thus, the proposed mechanism sought to satisfy these four essential conditions without the use of CNTs, suggesting a possible route toward highly processable long-chain carbyne.…”
mentioning
confidence: 99%